In vitro activity of Indian almond (Terminalia catappa) leaf crude extracts against selected dermatophytes - Colendres, Roxanne Joy B.; Pradera, Carl Leonard M. (Annals of Tropical Research, 2021)
Fungal infections caused by Trichophyton mentagrophytes, Aspergillus fumigatus, and Malassezia pachydermatis are among the major contributors to multisystemic health problems such as dermatitis, otitis, and respiratory disorders among humans and animals. This study was conducted to determine the in vitro antifungal activity of Terminalia catappa leaf crude aqueous and ethanolic extracts against these fungal pathogens by measuring the zone of inhibition (ZI) using the agar well diffusion technique. Qualitative phytochemical screening tests were also performed to determine bioactive compounds present in the plant extract. Results show that the plant’s crude aqueous (CAE) and ethanolic extracts (CEE) were found to be effective against all test fungi. M. pachydermatis showed susceptibility towards CAE and CEE from T1 (100%), T2 (75%), T3 (50%) and T4 (25%), with the highest mean ZI of 18.33mm and 13.33, respectively. On the other hand, T. mentagrophytes was inhibited by CAE and CEE at T1 (100%), T2 (75%) and T3 (50%) with the highest mean ZI of 9.67mm and 10.33mm, respectively. At the same time, it was observed that A. fumigatus had reactive sensitivity towards CAE and CEE at T1 (100%) and T2 (75%), with the highest mean ZI of 9.33mm and 10.33mm, respectively. Moreover, phytochemical tests showed that the plant’s leaf crude extracts contain alkaloids, saponins, and tannins, which could potentially inhibit fungal growth.